The Existence of Awig-Awig as a Basis in the Development of Hidden Canyon Tourism Destinations by Local Communities in Guwang Village, Gianyar District, Bali - Wiraharja, I Putu Gede Satria; Adyatma, I Wayan Chandra; Nida, Desak Rurik Pradnya Paramitha (Institut Pariwisata dan Bisnis Internasional, 2023)
According to Koentjaraningrat (2003: 76) the cultural value system is the highest and most abstract level of customs because cultural values consist of concepts regarding everything that is considered valuable and important by society so that it can function as a guide in their lives. This can be seen in the various rules applied in Guwang Village, such as not being allowed to sell land because the land belongs to the adat village; it is forbidden to cut down trees without village permission; for tourists who want to visit the Hidden Canyon Beji Guwang tour, they must obey the established rules, such as wearing a scarf and not entering the temple during menstruation; and tourists are also expected not to visit sacred places past the specified time. The research method used is qualitative with a qualitative descriptive research approach that aims to describe, describe, summarize various conditions, situations or variables that arise in the community that are the object of research. This research will be conducted in Hidden Canyon Tourist Destination, Guwang. by applying a purposive random sampling data collection technique. Overall, awig-awig has a very important role in the development of Hidden Canyon tourist destinations. Through the implementation of awig-awig, Hidden Canyon can be preserved, maintain the culture and social life of the local community, and provide a safe and comfortable experience for visitors. Thus, awig-awig becomes a strong foundation in the development of sustainable and responsible tourist destinations in Hidden Canyon.